Transfection of human CD59 complementary DNA into rat cells confers resistance to human complement. - Walsh, L; Tone, M; Waldmann, H (1991)
We have examined the role of the human CD59 antigen in inhibiting complement-mediated lysis by transfer and expression of a CD59 cDNA in rat cells. A cDNA encoding CD59 was subcloned into the expression vector pSFSVneo and stably transfected into the rat T cell line NB2-6TG. Indirect immunofluorescence staining using the anti-CD59 monoclonal antibody YTH53.1 demonstrated the presence of human CD59 antigen on transfected cells and its attachment to the cell surface by a rat glycolipid anchor. Transfected cells were found to contain a single 3.3-kb species of CD59 mRNA by Northern blot hybridization. Immunoblotting revealed that this encoded a protein band of the same size as that observed in human erythrocytes. To determine the biological effect of expression of human CD59 in rat cells, an assay was devised which measured the relative lysis of transfected cells compared to untransfected cells in the presence of human complement and a lytic monoclonal antibody. It was observed that CD59-transfected rat cells are less susceptible to lysis by human complement and that this effect was blocked by a F(ab')2 fragment of YTH53.1. These experiments provide a direct demonstration that CD59 can function as an homologous complement restriction factor for nucleated cells.